Trend dan hasil penggunaan model pembelajaran pendidikan jasmani (systematic literature review) - Maesara, Nadila; Rahmat, Alit; Carsiwan, Carsiwan (Jurnal Porkes, 2023)
The learning model of education is the planning or pattern used for instructional activities in the implementation of learning that can happen to the maximum. The aim of this research is to review the scientific literature on research trends and results of the use of learning models in physical education. The method used is a systematic literature review. This research search uses Harzing's publish or perish application by setting up a Google Scholar database with a time range of the last 10 years to select articles that can contain information about the use of the learning model of physical education. Research is guided by (preferred reporting items for systematic review and meta-analyses). The search results were 487 articles downloaded in 2014–2023, with 88 final articles being the result of a process of filtering inclusion and exclusion according to criteria with gradual and systematic selection. The findings are in line with the analysis of the systematic literature survey, which found that the trend of using the learning model of physical education varied, with cooperative learning becoming the main model most explored from year to year. The use of innovative and relevant learning models can improve student participation, learning outcomes, health and physical condition, motivation, and student involvement in the learning process.